Analysis of the Mathematical Communication Ability of Pre-Service Mathematics Teachers through Online Learning during the Covid-19 Pandemic - Sumargiyani Sumargiyani; Bidayatun Nafi'ah (Hipotenusa : Journal of Mathematical Society, 2020)
During the current Covid-19 pandemic, the learning system in all educational institution is shifted from face to face to online learning, including universities. This study aims to describe the results of the mathematical communication skills of class B students of Mathematics Education from Ahmad Dahlan University for the 2019/2020 academic year during online learning during the Covid-19 pandemic and to examine students' mistakes in solving differential calculus problems regarding the minimum, maximum material. This study employed descriptive qualitative research. The research instrument used is a test and interview guide. The data are collected using tests and interviews. The research subjects were selected by stratified random sampling technique so that 6 students are classified into high, medium and low categories. The questions are in the form of a description of one question with six questions. The results showed that students' mathematical communication skills on indicators (1) restating information was done appropriately, (2) writing down ideas or problem-solving steps clearly and precisely, some were not thorough, (3) presenting information using graphic images again. There are still things that they couldn't understand and (4) Writing down the answers according to what is known and are asked using mathematical formulas, some are still wrong because they are not accurate.